Protein deubiquitylase USP3 stabilizes Aurora A to promote proliferation and metastasis of esophageal squamous cell carcinoma - Ke Shi (BMC, 2021)
Abstract Aurora A kinase is a cell cycle regulator that is dysregulated in several different malignancies. Nevertheless, its regulatory mechanisms are still not fully understood. Here, we report that ubiquitin specific peptidase 3 (USP3) promotes proliferation and metastasis of esophageal squamous cell carcinoma (ESCC) cells by mediating deubiquitination of Aurora A. Analysis of human clinical samples indicated that USP3 and Aurora A are highly expressed in ESCC. Cellular experiments confirmed that high expression of USP3 and Aurora A in ESCC cells promoted malignant cell proliferation and invasion. In this mechanism, USP3 leads to suppression of Aurora A ubiquitination, resulting less proteasome degradation. We constructed the deubiquitinated mimetic K143R of Aurora A and found that K143R significantly promoted the proliferation and invasion of ESCC cells and was not regulated by the deubiquitination of USP3. Moreover, Aurora A K143R potentiated the kinase activity of Aurora A in ESCC cells. Thus, our findings demonstrate that the tumorigenic feature of ESCC is in part mediated by USP3-facilitated deubiquitination of Aurora A.